2021
DOI: 10.3389/fcell.2021.655440
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctionalized Structure and Ingredient Mimicking Scaffolds Achieving Recruitment and Chondrogenesis for Staged Cartilage Regeneration

Abstract: It remains scientifically challenging to regenerate injured cartilage in orthopedics. Recently, an endogenous cell recruitment strategy based on a combination of acellular scaffolds and chemoattractants to specifically and effectively recruit host cells and promote chondrogenic differentiation has brought new hope for in situ articular cartilage regeneration. In this study, a transforming growth factor-β3 (TGF-β3)-loaded biomimetic natural scaffold based on demineralized cancellous bone (DCB) and acellular car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Among many biomaterials, decellularized cartilage extracellular matrix (ECM) has been widely used because of its outstanding biocompatibility and biochemical cue retention [ 8 , 9 ]. Previous studies by our group have also demonstrated the positive effect of ECM on cartilage regeneration [ 10 , 11 ]. However, traditional ECM scaffolds are usually lyophilized.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Among many biomaterials, decellularized cartilage extracellular matrix (ECM) has been widely used because of its outstanding biocompatibility and biochemical cue retention [ 8 , 9 ]. Previous studies by our group have also demonstrated the positive effect of ECM on cartilage regeneration [ 10 , 11 ]. However, traditional ECM scaffolds are usually lyophilized.…”
Section: Introductionmentioning
confidence: 67%
“…Decellularized cartilage ECM was prepared by a combination of chemical and physical methods based on previous studies with slight modifications [ 10 , 11 , 25 ]. The specific experimental procedure is detailed in Supplementary File section 1 .1.…”
Section: Methodsmentioning
confidence: 99%
“…It has been well established that sufficient ESPCs are crucial for the meniscal healing process; however, the inherent recruitment and mobilization of ESPCs to the injured sites are inadequate for the repair of meniscal injury. 29 , 30 , 39 Although some chemokines and GFs, such as stromal cell‐derived factor‐1 and platelet‐derived GF‐BB, have been used to promote ESPC migration toward meniscal injury sites, the nonspecific mobilization induced by these factors, including the migration of proinflammatory or endothelial cells, might excessively activate inflammatory responses and thus impede meniscal regeneration. 40 , 41 Therefore, it is important to discover a chemoattractant that can specifically recognize and efficiently recruit ESPCs for endogenous meniscal regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we also found that cartilage-derived extracellular matrix scaffolds can promote stem cell migration, proliferation, cartilage differentiation, and enhance in vivo cartilage defect repair; therefore, it can be considered a promising alternative tissue engineering scaffold for the treatment of articular cartilage defects [12,13]. However, this cartilage-derived matrix, though a promising biomaterial for cartilage regeneration, still has some challenges.…”
Section: Of 15mentioning
confidence: 99%